2005
DOI: 10.2337/diacare.28.4.910
|View full text |Cite
|
Sign up to set email alerts
|

Increased Urinary Albumin Excretion, Insulin Resistance, and Related Cardiovascular Risk Factors in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -While the relevant role of insulin resistance in the pathogenesis of increased urinary albumin excretion (UAE) is well established in type 1 diabetes, its contribution in type 2 diabetes is controversial. Our aim was to investigate whether insulin resistance was associated with increased UAE in a large cohort of patients with type 2 diabetes. RESEARCH DESIGN AND METHODS-A total of 363 men and 349 women, aged 61 Ϯ 9 years, with a disease duration of 11 Ϯ 9 years and HbA 1c levels of 8.6 Ϯ 2.0% were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 33 publications
4
61
2
Order By: Relevance
“…Cigarette smoking, which is five times more prevalent among Persian men compared to women, 26 leads to reduced relaxant responses of the cutaneous microcirculation 27 as well as to blunted basal and stimulated nitric oxide bioactivity. 28 Consistent with the findings in the present study, De Cosmo et al 29 showed that, in patients with type 2 diabetes, increased urinary albumin excretion is associated with cardiovascular risk factors, which is significantly higher in men than in women. In a study on healthy individuals, Verhave et al 30 showed that cardiovascular risk factors and urinary albumin excretion rate are significantly correlated only in men.…”
Section: Discussionsupporting
confidence: 81%
“…Cigarette smoking, which is five times more prevalent among Persian men compared to women, 26 leads to reduced relaxant responses of the cutaneous microcirculation 27 as well as to blunted basal and stimulated nitric oxide bioactivity. 28 Consistent with the findings in the present study, De Cosmo et al 29 showed that, in patients with type 2 diabetes, increased urinary albumin excretion is associated with cardiovascular risk factors, which is significantly higher in men than in women. In a study on healthy individuals, Verhave et al 30 showed that cardiovascular risk factors and urinary albumin excretion rate are significantly correlated only in men.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with experimental data suggesting that insulin resistance and hyperglycemia contribute to malfunction and loss of podocytes, which are considered initial steps in the development of diabetic nephropathy and albuminuria (10)(11)(12)(13). Clinical studies addressing this issue were mainly performed in diabetic patients and have largely, but not consistently, confirmed an association between insulin resistance and microalbuminuria in this setting (10)(11)(12)(13)(14)(15)(16)(17)(18). Data in nondiabetic populations are sparse and show conflicting results (19)(20)(21)(22).…”
supporting
confidence: 50%
“…Furthermore insulin resistance, a powerful predictor of cardiovascular events, is seen even when whole-kidney GFR still is normal (53). This finding is of note because insulin resistance also is a feature of microalbuminuria (54) and a predictor of microalbuminuria in patients with type 2 diabetes (55). Damaged endothelial cells presumably are more sensitive to the injurious effects of further insults, e.g., elevated BP, analogous to the increased susceptibility of glomeruli to higher BP in diabetes (56).…”
Section: Potential Pathogenetic Mechanismsmentioning
confidence: 65%